THE ROLE OF PARALINGUISTIC MEANS IN SPEECH IMPACT - Madumarova Ziyoda Latibovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
This scientific article also provides detailed information about the culture of speech.